An agenda for the Management of contemporary Sustainable houses - Ifeanyi Obi (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
The evolution of sustainable design and Construction Management over the past ten years has produced a lot of literature on environmental sustainability and development. But despite this progress in the last ten years, it is still a big challenge to designers, architects, landscape designers, etc. and all other professions that are related to the field of environmental science. . The goal of this paper is to simply create a framework for a more accurate approach towards sustainable planning, design and development. The Objective of this paper includes to architecturally defining energy sustainable design in our sustainable Buildings; it is also to stress the concept of green building through design guidelines. This paper outlines, recommend and also create an architectural design for sustainability and eliminate unsustainable elements in our building.